2017
DOI: 10.1149/2.0031801jss
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the Spectroscopic Properties of α-LiAlO2: Mn4+

Abstract: The energy position of the 2 E g → 4 A 2g emission transition of Mn 4+ in α-LiAlO 2 is identified and the electronic energy levels calculated using the exchange charge model of crystal field theory. The results of our calculations yield the crystal field splitting and Racah parameters of Dq = 2351 cm −1 , B = 650 cm −1 and C = 3469 cm −1 , with C/B = 5.3. The calculated Mn 4+ energy levels are in good agreement with the experimental spectra that have been presented in the literature. A study that develops the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It has been established that Mn 4+ dopants preferably occupy the octahedral sites in most host lattices due to the attainment of large crystal field stabilization energy [27,28] . The α-LiAlO 2 synthesized via sol-gel technique has been reported by Iwamoto et al [29] and Mn 4+ ion exhibits luminescence in the spectral regions around 620-700 nm originating from 2 E g → 4 A 2g transition of Mn 4+ and the associated vibronic bands [25] . The PL spectrum of α-LiAlO 2 :Mn 4+ prepared by SSR (700 •C) exhibits emission peaks around 674 nm (in Figure 3), similar to literature reported elsewhere [25,29] .…”
Section: Mass Preparation Of Lialomentioning
confidence: 90%
See 2 more Smart Citations
“…It has been established that Mn 4+ dopants preferably occupy the octahedral sites in most host lattices due to the attainment of large crystal field stabilization energy [27,28] . The α-LiAlO 2 synthesized via sol-gel technique has been reported by Iwamoto et al [29] and Mn 4+ ion exhibits luminescence in the spectral regions around 620-700 nm originating from 2 E g → 4 A 2g transition of Mn 4+ and the associated vibronic bands [25] . The PL spectrum of α-LiAlO 2 :Mn 4+ prepared by SSR (700 •C) exhibits emission peaks around 674 nm (in Figure 3), similar to literature reported elsewhere [25,29] .…”
Section: Mass Preparation Of Lialomentioning
confidence: 90%
“…The α-LiAlO 2 synthesized via sol-gel technique has been reported by Iwamoto et al [29] and Mn 4+ ion exhibits luminescence in the spectral regions around 620-700 nm originating from 2 E g → 4 A 2g transition of Mn 4+ and the associated vibronic bands [25] . The PL spectrum of α-LiAlO 2 :Mn 4+ prepared by SSR (700 •C) exhibits emission peaks around 674 nm (in Figure 3), similar to literature reported elsewhere [25,29] . The PLE spectrum is typical for Mn 4+ ions, consisting of two broad bands from the 4 A 2g → 4 T 2g and 4 A 2g → 4 T 1g transitions of Mn 4+ and the charge transfer of Mn 4+ -O 2- [30] .…”
Section: Mass Preparation Of Lialomentioning
confidence: 90%
See 1 more Smart Citation
“…24 We examined cases where the octahedral groups share corners (as in the ABO 3 and A 2 B ' B '' O 6 perovskites) or edges and faces as in α-LiAlO 2 , Sr 4 Al 14 O 25 and CaAl 12 O 19 . 24 It was concluded that a highly symmetrical octahedral moiety increases "Mn 4+ -ligand" bonding covalence. The resulting emission spectrum is in the deep red because of the lowering of the 2 E g → 4 A 2g emission transition energy.…”
mentioning
confidence: 99%
“…24 We examined cases where the octahedral groups share corners (as in the ABO 3 In this paper, we report the synthesis and spectroscopic properties of the double perovskite La 2 LiSbO 6 activated with Mn 4+ . For comparative purposes, we also evaluate the spectroscopic data of the double perovskite, La 2 MgTiO 6 :Mn 4+ , which has been reported in the literature.…”
mentioning
confidence: 99%